Microalgae Aurantiochytrium Sp. Increases Neurogenesis and Improves Spatial Learning and Memory in Senescence-Accelerated Mouse-Prone 8 Mice - Sasaki, Kazunori; Geribaldi-Doldán, Noelia; Wu, Qingqing; Davies, Julie; Szele, Francis G.; Isoda, Hiroko (Frontiers in Cell and Developmental Biology, 2021)
Much attention has recently been focused on nutraceuticals, with minimal adverse effects, developed for preventing or treating neurological diseases such as Alzheimer's disease (AD). The present study was conducted to investigate the potential effect on neural development and function of the microalgae Aurantiochytrium sp. as a nutraceutical. To test neuroprotection by the ethanol extract of Aurantiochytrium (EEA) and a derivative, the n-Hexane layer of EEA (HEEA), amyloid-β-stimulated SH-SY5Y cells, was used as an in vitro AD model. We then assessed the potential enhancement of neurogenesis by EEA and HEEA using murine ex vivo neurospheres. We also administered EEA or HEEA to senescence-accelerated mouse-prone 8 (SAMP8) mice, a non-transgenic strain with accelerated aging and AD-like memory loss for evaluation of spatial learning and memory using the Morris water maze test. Finally, we performed immunohistochemical analysis for assessment of neurogenesis in mice administered EEA. Pretreatment of SH-SY5Y cells with EEA or the squalene-rich fraction of EEA, HEEA, ameliorated amyloid-β-induced cytotoxicity. Interestingly, only EEA-treated cells showed a significant increase in cell metabolism and intracellular adenosine triphosphate production. Moreover, EEA treatment significantly increased the number of neurospheres, whereas HEEA treatment significantly increased the number of β-III-tubulin+ young neurons and GFAP+ astrocytes. SAMP8 mice were given 50 mg/kg EEA or HEEA orally for 30 days. EEA and HEEA decreased escape latency in the Morris water maze in SAMP8 mice, indicating improved memory. To detect stem cells and newborn neurons, we administered BrdU for 9 days and measured BrdU+ cells in the dentate gyrus, a neurogenic stem cell niche of the hippocampus. In SAMP8 mice, EEA rapidly and significantly increased the number of BrdU+GFAP+ stem cells and their progeny, BrdU+NeuN+ mature neurons. In conclusion, our data in aggregate indicate that EEA and its constituents could be developed into a nutraceutical for promoting brain health and function against several age-related diseases, particularly AD.